Neuropilin-2 mediates lymphangiogenesis of colorectal carcinoma via a VEGFC/VEGFR3 independent signaling. Issue 2 (28th March 2015) - Ou, Juan-Juan; Wei, Xing; Peng, Yuan; Zha, Lin; Zhou, Rong-Bin; Shi, Hang; Zhou, Qi; Liang, Hou-Jie
Highlights: NRP2 expression levels of LECs are significantly correlated with the density of tumor lymphatic vessels in CRC. Activation of NRP2 in LECs substantially increases their migration, sprouting, and tubulogenesis capacity. NRP2 activation promotes CRC lymphangiogenesis via activating integrinα9β1/FAK/Erk signaling independent of VEGF pathway. NRP2 is a potential therapeutic target in preventing lymphatic metastasis of CRCs. Abstract: Lymphangiogenesis critically contributes to the lymphatic metastasis of colorectal carcinomas (CRCs), but the underlying mechanism of CRC lymphangiogenesis remains largely elusive. We have previously demonstrated that Semaphorin-3F (SEMA3F) is critically involved in CRC metastasis, and the receptor of SEMA3F, neuropilin-2 (NRP2), originally described as an axon guiding chemorepulsant implicated in nerve development, has been suggested in promoting lymphangiogenesis via acting as an obligate co-receptor of VEGFR3 cooperatively enhancing the activity of VEGF-C. Our present study revealed that in colorectal carcinomas, NRP2 expression levels of tumor-associated lymphatic endothelial cells (LECs) are significantly correlated with the density of tumor lymphatic vessels. In vitro, activation of NRP2 in LECs substantially facilitates their migration, sprouting, and tubulogenesis capacity via regulating the rearrangement of cytoskeleton polarity. In vivo model further showed that in the xenografts generated from SEMA3F knockdown CRC cells, NRP2 is substantially activated in tumor-associated LECs, resulting in a significantly increased tumor lymphangiogenesis. Further evidence demonstrated that CRC cell induces the activation of NRP2 in LECs to promote tumor lymphangiogenesis via integrinα9β1/FAK/Erk pathway independent VEGF-C/VEGFR3 signaling. Our study for the first time revealed the novel molecular mechanism of NRP2-mediated-lymphangiogenesis in CRCs, suggesting NRP2 as a potential therapeutic target in preventing lymphatic metastasis of CRCs.